‘Medical clearance’ and referral to liaison psychiatry: a national service evaluation - George Gillett; Sophie Westwood; Alex B. Thomson; William Lee (BJPsych Bulletin, 2024)
Aims and method The prevalence of delaying psychiatric care until the patient has received ‘medical clearance’, and the definitions and understanding of ‘medical clearance’ terminology by relevant clinicians, are largely unknown. In a service evaluation of adult liaison psychiatry services across England, we explore the prevalence, definitions and understanding of ‘medical clearance’ terminology in three parallel studies: (a) an analysis of trust policies, (b) a survey of liaison psychiatry services and (c) a survey of referring junior doctors. Content and thematic analyses were performed.